Prekancerózy v gynekologii - endometrium - Feranec, R; Mouková, L; Chovanec, J (Klinicka onkologie, 2013)
Preinvasive lesions of the endometrium are histopathological and molecular alterations related to high-risk of uterine carcinoma development. Incidence has increasing tendency. Atypical endometrial hyperplasia is the preinvasive lesion of type I endometrial carcinoma, developing under a hyperestrogenic background. Carcinoma in situ of the endometrium is considered to be precursor lesion of type II endometrial carcinoma, first of all uterine serous carcinoma. Hysterectomy and bilateral oophorectomy is the main therapeutical modality in both preinvasive lesions of the endometrium. The hormonal therapy with progestogens is the possibility of fertility sparing approach in treatment of histological findings of atypical endometrial hyperplasia in young women. Even though preinvasive lesions of the endometrium are clearly defined, the possibilities of endometrial cancer screening are markedly limited.
Keywords: Endometrial Hyperplasia; preinvasive lesion - endometrium - atypic endometrial hyperplasia - carcinoma in situ of the endometrium; Female; Carcinoma in Situ; nádory endometria; Endometrial Neoplasms; prekancerózy; ženské pohlaví; Humans; karcinom in situ; Precancerous Conditions; lidé; hyperplazie endometria